A closer look into close packing: pentacoordinated silicon in a high-pressure polymorph of danburite. (2017) - Pakhomova, Anna; Bykova, Elena; Bykov, Maxim; Glazyrin, Konstantin; Gasharova, Biliana; Liermann, Hanns-Peter
No abstract available